Pendampingan Pastoral Terhadap Keluarga Nelayan - Donggala, Yelly Irene (Educatio Christi, 2020)
The sea is part of the vast universe created of God. The natural wealth that is stored in the sea is so extraordinary that it is not surprising that humans often share the wealth that is in the sea and take marine products in order for humans to try to make ends meet and to reveal the standard of living and human welfare. The process of increasing the standard of living of humans is also hunting fish in the sea so that there are some people who to make ends meet and even their families, they work in the middle of the sea as fishermen. In the Belang area, in the territory of the GMIM Bethlehem Minanga service area, there are several heads of families and adult males who are not yet married who work as fishermen. Working alone in the middle of the high seas for months or even years. The work of fishermen does have a very dangerous safety risk, while the family experiences a serious struggle when their husband or child is working in the middle of the sea. The purpose of this study is to describe the experience of pastoral care and the importance of pastoral care for fishermen and their families, so that those who work like this can be guided in improving their standard of living as well as to strengthen their faith and hope as believers in the Lord Jesus Christ.